Adaptive Governance Model in Cultural Preservation: Balancing Customary Obligations and Community Economy in Bali - I Gusti Agung Ayu Yuliartika Dewi; Komang Tri Putri Andriastuti Andriastuti (Journal of Social and Policy Issues, 2026)
This study aims to analyze the coordination patterns between the Bali Provincial Government and Desa Adat (Customary Villages) regarding cultural preservation and to evaluate the effectiveness of the current governance model. Methodologically, this study employs a qualitative approach through in depth interviews with key informants, including government officials, Majelis Desa Adat administrators, Bendesa Adat, and community members (krama). The results show that the current cultural governance model is protective-normative, focusing on institutional strengthening and budgetary support, yet it is not yet fully adaptive to the community's economic pressures. There is a noted imbalance between the symbolic value of culture and the actual economic capacity of residents, exacerbated by rising ceremonial costs and social expectations. Consequently, this study proposes an adaptive-collaborative governance model supported by four main pillars: flexible awig-awig regulation, needs based cultural subsidy schemes, digital transparency in customary fund management, and deliberative collaborative forums. In conclusion, the transformation toward an adaptive collaborative governance model is a structural necessity to maintain the balance between state authority, customary autonomy, and the socio-economic sustainability of the community. This integration is expected to ensure that the preservation of tradition remains proportional and inclusive, while guaranteeing social justice for the Balinese people amidst the dynamics of globalization.